2006
DOI: 10.1207/s15548430jlr3804_1
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Children to Become Fluent and Automatic Readers

Abstract: The purpose of the study was to examine the effects of two instructional approaches designed to improve the reading fluency of 2nd-grade children. The first approach was based on Stahl and Heubach's (2005) fluency-oriented reading instruction (FORI) and involved the scaffolded, repeated reading of grade-level texts over the course of each week. The second was a wide-reading approach that also involved scaffolded instruction, but that incorporated the reading of 3 different grade-level texts each week and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 44 publications
5
49
0
2
Order By: Relevance
“…Considering the benefits of reading aloud, it was reported that elementary school children in the U.S. were able to build automaticity of word recognition and acquire the proper prosodic aspects of English as EFL learners did (Kuhn et al, 2006;National Reading Panel, 2000). Fuchs et al (2001) proclaimed that being able to read aloud with accurate prosodic aspects could be one of the indicators of reading comprehension ability.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the benefits of reading aloud, it was reported that elementary school children in the U.S. were able to build automaticity of word recognition and acquire the proper prosodic aspects of English as EFL learners did (Kuhn et al, 2006;National Reading Panel, 2000). Fuchs et al (2001) proclaimed that being able to read aloud with accurate prosodic aspects could be one of the indicators of reading comprehension ability.…”
Section: Discussionmentioning
confidence: 99%
“…Estes resultados corroboram os que têm sido obtidos noutros estudos (STAHL;HEUBACH, 2005;KUNH et al, 2006;PADAK, 2008), efetuados com alunos do mesmo ano de escolaridade (2º ano) e cujo tempo de aplicação foi sensivelmente de um ano letivo. Estes estudos recorreram a estratégias muito semelhantes às que foram, posteriormente, utilizadas no PPFL, incluindo a complementação da intervenção em sala de aula com tarefas a efetuar em casa.…”
Section: Discussão Dos Resultadosunclassified
“…Os resultados obtidos em programas de treino da fluência em leitura têm sido encorajadores (HOFFMAN;CRONE, 1985;HOFFMAN, 1987;STAHL;HEUBACH, 2005;KUNH et al, 2006;PADAK, 2008;TUR-NER, 2012) A investigação clarificou, de forma inequívoca, a importância da fluência para a leitura em geral (que, por definição é compreender), mas os resultados da investigação demoram a chegar às práticas docentes. Como afirma Rasinski (2010), apesar das limitações que lhe são reconhecidas, a "Round Robin Reading" (que traduzimos por "leitura oral de carreirinha"), continua a ter o principal papel no ensino da leitura e é considerada pelos professores das séries iniciais como o principal ou único modo de desenvolver a fluência de leitura dos alunos.…”
Section: A Necessidade De Investir Na Fluência Em Leituraunclassified
“…In other words, students need to be afforded multiple opportunities to read problems at their independent/instructional level (Rasinski 2000;Rasinski and Padak 1996), or even their instructional/challenge level, when provided with teacher scaffolding (Kuhn 2005;Kuhn and Stahl 2003). Additionally, through repeated scaffolded exposures to text, students began to recognize orthographic patterns in words, experience various components of language, enhance their sight vocabulary, develop a quick and effortless ability to recognize words, and free up attention for higher levels of comprehension (Kuhn et al 2006). …”
Section: Recognizing Patterns Literal Comprehension Of Text Organizatmentioning
confidence: 99%